2005
DOI: 10.1007/s10562-004-3452-7
|View full text |Cite
|
Sign up to set email alerts
|

N-alkylation of aniline with ethanol over an industrial niobic acid catalyst ? influence of water formation on kinetics and selectivity

Abstract: The reaction of aniline with ethanol was carried out over an industrial niobic acid catalyst in a fixed bed reactor at atmospheric pressure and 220-260°C. The main products, N-ethylaniline and N,N-diethylaniline were formed consecutively. A kinetic study including a model discrimination between several Hougen/Watson type rate equations led to an Eley/Rideal mechanism, where the reaction of gas phase aniline with adsorbed ethanol is the rate determining step. As second adsorbing agent, water inhibits the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…NBS gave higher cellulose conversion and glucose yield, while NBP gave a higher HMF yield under the same reaction conditions. Previous works indicated that the acidity of niobic acid could be greatly improved via acid treatment, providing acidity equivalent to strong inorganic acids at low temperatures. During the process of cellulose hydrolysis in acidic conditions, glucose is generated on the Brønsted acid sites, while HMF is generated on the Lewis acid sites. , Results of hydrolysis reactions indicated the different modification effects of sulfuric acid and phosphoric acid on the effective acidity of catalyst, such as nature, strength, and amount of acid sites.…”
Section: Discussionmentioning
confidence: 99%
“…NBS gave higher cellulose conversion and glucose yield, while NBP gave a higher HMF yield under the same reaction conditions. Previous works indicated that the acidity of niobic acid could be greatly improved via acid treatment, providing acidity equivalent to strong inorganic acids at low temperatures. During the process of cellulose hydrolysis in acidic conditions, glucose is generated on the Brønsted acid sites, while HMF is generated on the Lewis acid sites. , Results of hydrolysis reactions indicated the different modification effects of sulfuric acid and phosphoric acid on the effective acidity of catalyst, such as nature, strength, and amount of acid sites.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional liquid acids such as sulfuric, hydrochloric, hydrobromic, and hydroiodic acids have been reported to catalyze the methylation of amines [102]. On the other hand, solid acids such as alumina [103][104][105][106], silica-alumina [107], faujasite [108], beta zeolite, EMT zeolites [109], AlPO 4 -5 [110,111], and niobic acid [112] have been used as catalysts in the gas-phase flow system, which requires no solvent, circumvents tedious separation procedures, and recycles the catalyst. These catalysts are chiefly used for the alkylation of aniline, because this reaction proceeds smoothly.…”
Section: Methylation Of Toluene (Equationmentioning
confidence: 99%
“…Eigene vorhergehende Forschungsarbeiten richteten sich auf die N-Alkylierung von Anilin mit Ethanol [6,7]. Eine kinetische Studie zeigte, dass die Reaktion über eine adsorbierte Ethoxy-Species abläuft.…”
Section: Problemstellungunclassified